Superior effectiveness of a newly developed nonadherent polyurethane-coated surgical patty for hemostasis - Otsuka, Yohei; Toyooka, Terushige; Takeuchi, Satoru; Tomiyama, Arata; Tomura, Satoshi; Wada, Kojiro (Asian Journal of Neurosurgery, 2021)
Background: Cotton patty is usually used to aspirate blood and cerebrospinal fluid to maintain a dry field. However, the cotton patty easily adheres to the vessels by capillary action, especially in combination with hemostat. Therefore, re-bleeding may be induced by removal of the cotton patty stuck to the vessel despite initial control of the bleeding. Methods: We have developed a new cotton patty (Non-Stina X®, Hakujuji, Co., Ltd., Tokyo, Japan) which does not adhere to the vessels. The newly developed cotton patty is made of 100% cotton, with only the contact surface coated with polyurethane film which prevents capillary action. The coated side includes many holes to allow aspiration from both sides. Results: The characteristics of four different surgical patties including our new patty which are available for surgical use in Japan were investigated. Transverse sections of four different surgical patties were investigated by light microscopy (magnification ×150). Our new cotton patty did not show any fluffing on the polyurethane-coated surface. However, other surgical patties showed some fluffing on their surfaces. The friction coefficients of four different surgical patties were investigated. Our new cotton patty had the lowest of the four neurosurgical patties. We confirmed the nonadherent characteristic using with hemostats of gelatinous sponge or fibrin glue-soaked oxidized cellulose cotton during hemostasis in neurosurgical procedures. The polyurethane-coated cotton patty could be removed easily from the hemostats without re-bleeding. Conclusions: The newly developed polyurethane-coated cotton patty is more effective for bleeding control from vessels with several types of hemostat due to the nonadherent characteristics.
Keywords: Clipping; hemostasis; microsurgery; polyester-coated surgical patty